A robust authentication technique using pixel value graphical password scheme / Dr. Mohd Afizi Mohd Shukran - Mohd Shukran, Mohd Afizi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
In decades, authentication system is relying on username and password as passphrase object for authentication process. The username and password mechanism bring major problem lately and raising the system developer worries on security for client server communication. Many methods and mechanisms are being introduced to overcome this authentication flaws. One of mechanism that has been introduce is graphical password mechanism on purpose to reduce human memory burden based on psychological study that shows human is better at recognizing and remembering images. However, the current method results many security flaws on graphical password authentication mechanism and require specific tool which is cannot be easily implement on any computer system platform. To overcome current method flaws, pixel value graphical password scheme is being introduced by combining the text-based password mechanism and graphical password mechanism where the authentication system extracting pixel value that resides in a digital image file. The extracted eight bits pixel value is used as the passphrase alongside with username during authentication process. The design and development of this method is based on identified graphical password enhancement and user requirement through literature review analysis.